An Analysis of Trademark Disputes Between MS Glow and PS Glow - Brian Jeremy Modami; Gunardi Lie (CV. Rayyan Dwi Bharata, 2023)
Some time ago there was a dispute between the skincare brands MS Glow and PS Glow. In this dispute, the thing that is disputed is the similarity of the brands of the two products. According to Law No. 20 of 2016 article 1, a mark is a sign that can be displayed graphically in the form of an image, logo, word name, letter, number, color arrangement in the form of 2. (two) dimensions and/or 3 (three) dimensions, sound, hologram, or a combination of 2 (two) or more of these elements to differentiate goods and/or services produced by persons or legal entities in the activity of trading goods and/or services. Furthermore, the article also mentions the matter of trademarks. A trademark is a brand that is used on goods that are traded by a person or several people together or a legal entity to differentiate them from similar goods. Collective Mark is a mark used for trading activities of goods and/or services with the same characteristics which are traded by several persons or legal entities together to differentiate goods and/or services of other types. Trademark rights are a form of IPR protection in which the brand owner registered are given an exclusive right to use their own mark that has been registered for trading activities of goods and/or services, or give permission to other parties to use the mark in question by means of a license. Trademark rights are regulated in Law NO. 20 of 2016 concerning brands and geographical indications.